Dual-Chamber microbial fuel cell for Azo-Dye degradation and electricity generation in Textile wastewater treatment - Ndive, Julius N.; Eze, Simeon Okechukwu; Nnabuife, Somtochukwu Godfrey; Kuang, Boyu; Rana, Zeeshan A. (Elsevier, 2025)
Textile wastewater, particularly azo dyes, poses significant environmental challenges due to its poor biodegradability and toxicity. This study explores a dual-chamber microbial fuel cell (MFC) for simultaneous wastewater treatment and electricity generation. The MFC consists of an anaerobic anode chamber and an aerobic cathode chamber, separated by a proton exchange membrane (PEM). Electroactive microorganisms in the anode chamber metabolize organic substrates, including azo dye contaminants, breaking them down into simpler by-products. Electrons released during this process flow through an external circuit to generate current, while protons migrate across the PEM to the cathode chamber for oxygen reduction. Electrochemically active microbes were isolated from azo-dye-contaminated soil, and their degradation abilities validated through assays. Optimized carbon-based electrodes and a Nafion 117 PEM were used to enhance conductivity and microbial activity. UV–Vis spectroscopy tracked dye degradation, with the absorbance peak of reactive yellow dye at 410 nm decreasing from 2.9 to 0.4, indicating effective azo-bond cleavage. The MFC achieved peak voltage and current outputs of 0.20 mV and 0.16 mA, respectively, demonstrating its dual functionality. Adding NaCl as a supporting electrolyte further improved ionic conductivity and performance. This study demonstrates MFC technology as a sustainable solution for industrial wastewater challenges, integrating microbial degradation with bioelectricity generation. Future work should address scalability, operational stability, and advanced electrode designs to enhance its practical applications.
Keywords: 4004 Chemical Engineering; 31 Biological Sciences; 40 Engineering; 3106 Industrial Biotechnology; Bioelectrochemical systems; UV–Vis spectroscopy; Carbon-based electrodes; Wastewater bioremediation; Nafion 117 membrane; Sustainable energy recovery